PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSETS (ROA) PADA PT CIPUTRA DEVELOPMENT TBK PERIODE 2013-2022 - Shella Permata Sari; Hendri Prasetyo (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of the Current Ratio and Debt to Equity Ratio on Return on Assets in PT Ciputra Development Tbk for the 2013-2022 period. This type of research uses a quantitative method, the data used is in the form of secondary data obtained from the official website of https://www.ciputradevelopment.com. Data analysis techniques used the Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, Multiple Linear Regression Analysis, Correlation Coefficient Test, Determination Coefficient Test, Hypothesis Test using SPSS software version 26. The results of this study show that the Current Ratio (CR) partially has a negative and significant effect on the Return on Assets (ROA) in PT Ciputra Development Tbk for the period 2013-2022 based on a significant value of < 0.05 (0.003 < 0.5) and tcount > ttable (-4.155 > 2.365). And simultaneously the Current Ratio (CR) and Debt to Equity Ratio (DER) have a significant effect on Return On Assets (ROA). This is evidenced by the value of (Fcal 13.556 > Ftabel 4.737) with a significant value of (0.004 < 0.05)